Urinary bisphenol A detection is significantly associated with young and obese Thai children - Sopon Pornkunwilai (2018)
Background: Bisphenol A (BPA), a xenoestrogenic monomer, is one of the most common industrial chemicals used in epoxy coatings for canned food and other consumer items. There is only limited information regarding the potential health risks from BPA exposure in children and adolescents from Asian countries. Objective: To detect and determine urinary BPA concentrations, and identify possible association between urinary BPA levels, demographic characteristics, and BPA exposure risks in Thai children and adolescents. Methods: A cross-sectional study was conducted in 376 children and adolescents aged 3-18 years from kindergarten, elementary, and middle schools in Bangkok, Thailand. Urinary concentrations of total BPA were determined by liquid chromatography tandem mass spectrometry (LC-MSMS). Anthropometric data and questionnaires regarding BPA exposure risks were collected. Results: BPA was detected in 283 of 376 urine samples (75.3%) with a median adjusted BPA 0.53 μg/g creatinine (range 0.04-1.12). Thirty-one participants (9%) were overweight and 39 (11%) were obese. The BPA detection rate was significantly higher in obese children (OR 3.42, 95% confidence interval (CI) 1.18-9.95, P = 0.02) compared with children of normal weight. BPA was detected more often in younger children (3-6 years) when compared with children (6-10 years) and adolescents (10-18 years). There were no significant association between BPA levels and other demographic data or BPA exposure risks. Conclusions: BPA exposure in Thai children and adolescents may be lower than exposure in children from the United States, some European nations, and other Asian countries. Obese and younger children were significantly associated with BPA detection.